Effect of coronavirus disease lockdown on the physical and psychological attributes of Nigerian athletes - Oke, K. I.; Ogundiran, O. O.; Ogbouma, S.; Mbad, C. E. (African Journal of Medicine and Medical Sciences, 2021)
Background/ Objective: The aim of the study was to assess the effect of lockdown measures occasioned by COVID-19 pandemic on the physical and psychological characteristics of Nigerian athletes. Methods: An online survey involving 578 elite athletes was utilized, using an electronic questionnaire which sought information on respondents` socio-demographics, sports type, level of psychological distress, injury incidences management, and expectations or otherwise of financial support during the lockdown period. Data obtained were analyzed with descriptive and inferential statistics with SPSS version 21 with alpha set at <0.05.